ANALISIS SOAL UJIAN AKHIR SEMESTER BAHASA INDONESIA KELAS VII SMP NEGERI DI KOTA SIBOLGA - Grace Banjarnahor, Pretty; Prihasti Wuriyani, Elly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the quality of the Indonesian Language Final Examination (UAS) questions for grade VII of Public Junior High Schools in Sibolga City for the 2025/2026 Academic Year based on the implementation of the Independent Curriculum. The analysis focused on the suitability of the questions to the Learning Outcomes (CP) and Learning Objectives (TP), the distribution of cognitive levels of the Revised Bloom's Taxonomy, and the characteristics of questions based on Higher Order Thinking Skills (HOTS). The research method used was descriptive qualitative with content analysis techniques. The research objects were UAS question script documents from Public Junior High Schools 2 Sibolga, Public Junior High School 3 Sibolga, and Public Junior High School 4 Sibolga. The results showed that the question material was generally in accordance with CP Phase D, but there were indicators of productive writing skills that had not been accommodated. The distribution of cognitive levels was still dominated by the Lower Order Thinking Skills (LOTS) and Middle Order Thinking Skills (MOTS) categories, while HOTS-categorized questions were still very limited. In fact, one school did not have HOTS-categorized questions at all. The conclusions of this study emphasize the need to improve teacher competency in developing assessment instruments, particularly in distributing cognitive levels proportionally and integrating stimuli that effectively demand students' critical and creative thinking skills.